INFLUENCE OF REGULAR SWIMMING LEARNING ON THE PARAMETERS OF THE RESPIRATORY SYSTEM - Svetlichkina A.A. ,; Medvedev I.N. ,; Komarov M.N. ,; Porubayko L.N. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the level of development of the respiratory system in experienced swimmers. Methods and structure of the study. The scientific work involved 37 young men who have been swimming every day for the last 2 years: during the day they swam for 1 hour - 12 people; swam for 40 minutes a day - 14 young men; swam for 30 minutes a day - 11 people. The assembled control group consisted of 17 young men who had never been involved in sports. The state of the respiratory system was taken into account and the results were statistically processed. Results and conclusions. In the case of regular swimming lessons, an increase in the volume and speed indicators of the respiratory system was revealed. Their greatest severity was in athletes who train for an hour a day. Apparently, swimming lessons, as training lengthens, increase the degree of development of the muscles of the upper shoulder girdle and chest while expanding the bronchi and increasing the available physical capabilities. As a result of learning to swim in the youthful body, the development of the pulmonary system and muscles, which provide the breathing process, is enhanced. This increases as the daily swimming sessions lengthen.